PsycEXTRA Dataset 2004
DOI: 10.1037/e302462005-001
|View full text |Cite
|
Sign up to set email alerts
|

Grandma and Grandpa Taking Care of the Kids: Patterns of Involvement

Abstract: verview Over the last decade, considerable media attention and public discussion have focused on the varied roles that grandparents play in family life. Much of this public attention has centered on grandparents who assume parental responsibilities for their grandchildren. 1 Similarly, grandparents are recognized for the active but temporary roles they assume during times of crisis or special need, such as in cases of a parental divorce or military deployment. 2 Yet child care provided in such contexts constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 3 publications
0
51
0
10
Order By: Relevance
“…Point estimates of the frequency of care vary somewhat between studies, but the gender gap is found consistently. For instance, Guzman (2004) reports that 52 % of U.S. grandmothers and 38 % of U.S. grandfathers provide some childcare, whereas Hank and Buber (2009), analyzing data from 10 European countries, report that 58 and 49 % of grandmothers and grandfathers care for grandchildren, respectively. Furthermore, grandfathers tend to provide childcare less often without their spouse (Uhlenberg and Hammill 1998) and are less often engaged in intensive care (Hank and Buber 2009).…”
Section: Variations In Grandparental Childcare By Gender and Kinshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Point estimates of the frequency of care vary somewhat between studies, but the gender gap is found consistently. For instance, Guzman (2004) reports that 52 % of U.S. grandmothers and 38 % of U.S. grandfathers provide some childcare, whereas Hank and Buber (2009), analyzing data from 10 European countries, report that 58 and 49 % of grandmothers and grandfathers care for grandchildren, respectively. Furthermore, grandfathers tend to provide childcare less often without their spouse (Uhlenberg and Hammill 1998) and are less often engaged in intensive care (Hank and Buber 2009).…”
Section: Variations In Grandparental Childcare By Gender and Kinshipmentioning
confidence: 99%
“…Earlier research relied on somewhat oversimplified measures of employment status and typically distinguished only two categories of labor force attachment: for instance, employed/not employed (Baydar and Brooks-Gunn 1998;Guzman 2004;Igel and Szydlik 2011;Wang and Marcotte 2007) or working/not working (Aasve et al 2012;Hank and Buber 2009;Lee and Bauer 2010;Uhlenberg and Hammill 1998). The most detailed measurement involved three categories: working full-time, working part-time, and not working (Luo et al 2012;Silverstein and Marenco 2001).…”
Section: Employment and Grandparental Childcarementioning
confidence: 99%
“…Evidence consistently shows that grandmothers are more likely to be engaged in it than grandfathers, particularly in case of intensive child care (Fuller-Thomson and Minkler 2001;Brandis 2003;Guzman 2004;Fokkema, Ter Bekke, and Dykstra 2008;Hank and Buber 2009;Igel and Szydlik 2011;Danielsbacka 2011;Ghysels 2011). Younger grandparents tend to provide more child care than older grandparents (Fuller-Thomson and Minkler 2001;Hank and Buber 2009).…”
Section: Characteristics Of Grandparents Parents and Childrenmentioning
confidence: 99%
“…Other parents choose grandparental child care because it is the most convenient. Using grandparental child care may also represent the only affordable or available option (Wheelock and Jones 2002;Brandis 2003;Guzman 2004;Fergusson, Maughan, and Golding 2008 (Hank and Buber 2009). A European aged 50 years and over spends on average 0,5 hours per day looking after grandchildren, while she or he devotes on average 1,5 hours working in the market and 0,3 hours helping relatives, friends or neighbours (Croda and Gonzalez-Chapela 2005).…”
Section: Grandparents and Child Care In Europementioning
confidence: 99%
“…A number of supplementary independent variables were included, mainly as controls, in order to avoid possible confounding influences related to demographic characteristics, availability, health and attitudes (Attias-Donfut et al, 2005;Baydar and Brooks-Gunn, 1998;Guzman, 1999Guzman, , 2004Hank and Buber, 2009;Kuhltau and Mason, 1996;Presser, 1989;Silverstein and Marenco, 2001;Vandell et al, 2003). Among those were gender of the selected child (male ¼ 0, female ¼ 1), allowing for tracing lineage patterns; distance to the selected child, ranging from same household (0) to more than 500 km away (8); educational level of the selected child (from none/little ¼ 0 to higher university level ¼ 6); whether the selected child had a partner/spouse (1) or not (0), as well as the selected child's age in years above 25.…”
Section: Methodsmentioning
confidence: 99%